How Community Education Can Prevent Traffic Violation and Traffic Accident? (Case of Balikpapan City) - Meidika Dwiantara Putra Jati (Police Studies Review, 2021)
This research is based on the number of traffic accidents involving students in the city of Balikpapan, which always has an increasing percentage when compared to the total number of accidents in the last 3 years (2018-2020), therefore researchers are interested in researching the implementation of Traffic Education for students carried out by the Dikyasa Unit of the Balikpapan Police Satlantas. Based on this background, three problem formulations were formulated, namely the Implementation of the Social Education Education, the influencing factors, and the optimization of the Social Education Education. This type of research is a field research with a qualitative approach, the data sources used are primary and secondary data collection techniques. in the form of interviews, observations and document studies. Data validity using triangulation technique. Data analysis techniques in the form of data reduction, data presentation, and drawing conclusions. From the results of the research carried out, it was found that the implementation of the Dikmas Then for students was still not running optimally, which was caused by several internal and external factors, internal factors including the lack of personnel from the Dikyasa unit in terms of quantity, not optimal budget management carried out, and the ability of personnel in delivering the Dikmas Traffic which is less varied and innovative, while the external factors come from students as the object of the implementation of the Dikmas Then. Based on the results of the study, the authors have several suggestions for the Balikpapan Police Headquarters to prepare all the needs to support the Optimal Traffic Dikmas implementation, including increasing the number of Dikyasa Unit personnel, increasing the budget and budget management which must be even better, coordinating with other Satker related to message delivery. Kamseltibcar Then to students, and the need for new innovations in the delivery of Dikmas Then to students in the City of Balikpapan